Leucocyte-poor-platelet-rich plasma intra-operative injection in chondral knee injuries improve patients outcomes. A prospective randomized trial - Danieli, Marcus Vinicius; Guerreiro, João Paulo Fernandes; Queiroz, Alexandre Oliveira; da Rosa Pereira, Hamilton [UNESP]; Cataneo, Daniele Cristina [UNESP] (Springer Nature, 2021)
Purpose: Evaluate the effects of intra-operative leucocyte-poor-platelet-rich plasma (PRP) (type P3-Bβ with endogenous activation) injection in International Cartilage Repair Society (ICRS) grade III knee chondral injuries treated by chondroplasties, to increase and ameliorate the repair tissue. Methods: Patients were divided into two groups. Group A (control) consisted of 31 patients and Group B (PRP) 33 patients, totaling 64 patients analyzed. Patients also could had associated injuries (meniscal and/or ACL) being equally divided between both groups to avoid bias. PRP was injected at the end of surgery in group B. The patient outcomes were assessed using subjective International Knee Documentation Committee (IKDC) form, Knee Injury and Osteoarthritis Outcome Score (KOOS), and Tegner activity forms, prior to the surgery and three, six, 12, and 24 months after surgery (medium-term follow up). Results: IKDC and KOOS scores showed increase at each evaluation time points after surgery in both groups, but the treated Group (B) showed a higher increase with statistically significant difference. The Tegner activity scores were higher for the treated group only at six and 12 months. Conclusion: Based on the subjective IKDC, KOOS, and Tegner scores, those patients affected by ICRS grade III chondral injuries undergoing arthroscopic chondroplasty who were also treated with PRP showed better and faster outcomes than the control group. Independently from the associated injury (meniscal or ACL). This difference could be measured for up to two years.
Keywords: Arthroscopy; Articular cartilage; Knee; Platelet-rich plasma